Diagnóstico del volumen de tránsito y medición de velocidad a la Intersección de la Calle 17 con Carrera 15 de la Ciudad de Pereira (2020)
Aware that the road problems in the city of Pereira can be diagnosed by the academy, this proposal has been formulated from a group of university students in the last semester of Civil Engineering at Antonio Nariño University campus located in Pereira. The proposal explains a road diagnosis at the traffic light intersection on 17th street between road 14th and 15th in Pereira. There was a technical survey conducted of the amount of vehicles and the speed limit, which by the way, showed the type of vehicle that transit those roads often and the hours of maximum demand, or peak hours, all analyzed both for a typical day and an atypical day of the week, in a typical month of the year. The data obtained from the survey were used to study the current status of the functionality of this road intersection, but also to determine the factors that influence the mobility problem and to think about one or more solutions that studied and review with the aim to improve traffic flow and reducing travel times so that its users take less time to reach their destinations. As this road diagnosis is a real and technical study that was carried out rigorously under established parameters at a junction that reports traffic jams and lack of functionality, it is expected to be analyzed by entities such as: Area Metropolitana Centro Occidente AMCO and Instituto de Movilidad de Pereira, with the goal of generating a practical and economic solution that will be beneficial for the roads users.